An appraisal of cinnamyl sulfonamide hydroxamate derivatives (HDAC inhibitors) for anti-cancer, anti-angiogenic and anti-metastatic activities in human cancer cells. (25th June 2016) - Reddy, Neetinkumar D.; Shoja, M.H.; Biswas, Subhankar; Nayak, Pawan G.; Kumar, Nitesh; Rao, C. Mallikarjuna
Abstract: Multiple genetic mutations along with unusual epigenetic modifications play a major role in cancer development. Histone deacetylase (HDAC) enzyme overexpression observed in the majority of cancers is responsible for tumor suppressor gene silencing and activation of proto-oncogenes to oncogenes. Cinnamic acid derivatives exhibit anti-cancer potential through HDAC enzyme inhibition. We have synthesized a few cinnamyl sulfonamide hydroxamate derivatives (NMJ-1, -2 and -3) by already published in-house procedures and their purity, and chemical characterization were performed by NMR, mass spectrometry and elemental analysis. The anti-cancer activities were also evaluated against colon cancer. The rationale for synthesis was based on bioisosterism concept. To take the work forward, these compounds were considered for in vitro anti-angiogenic and anti-metastatic activities in cancer cells. The effectiveness of these compounds was determined by SRB assay. The compounds showed cancer cell cytotoxicity (IC50 range of 5.7 ± 0.43 to 20.5 ± 1.9 μM). The mechanism of compound-induced cell death involves an intrinsic apoptosis pathway which was supported by the following: increase in apoptotic index, arrest in cell cycle at G2 /M phase, increase in annexin V binding and induction of p21 Waf1/Cip1 expression in the treated cells. Further, their target modulating effect, measured as the expression of acetyl-H3 histone and acetyl α-tubulin was determined by Western blots. Hyper acetylation of H3 histone and α-tubulin were observed. Furthermore, increased expression of cleaved caspase-3, cleaved PARP, total Bad was estimated by ELISA. The anti-angiogenic effect was examined through cobalt (II) chloride (CoCl2 )-induced HIF-1α expression, where the compounds reduced the expression of induced HIF-1α. In addition, their anti-metastatic ability was determined through phorbol-12-myristate-13-acetate (PMA)-induced expression of MMP-2 and -9 by Western blotting and gelatin zymography. Inhibition of malignant cell migration was assessed by scratch wound assay. The compounds showed a decrease in cell migration and inhibition of induced MMP-2 and MMP-9 expression. NMJ-2 exhibited comparable activity to that of standard SAHA. Our findings indicate that NMJ series of compound have potent in vitro anti-cancer, anti-angiogenic and anti-metastatic activity through HDAC enzyme inhibition. Graphical abstract: Highlights: NMJ series of compounds exhibited broad spectrum anticancer activity. Compounds induced H3 histone and α-tubulin acetylation in MCF-7 cancer cells. Compounds induced expression of p21 Waf1/Cip1, cleaved caspase-3 and PARP, total Bad. Compounds reduced cancer cell migration ability and lowered MMP-2, -9 expression. Compounds exhibited anti-angiogenic potential by reducing HIF1-α expression.